Match each expression with an equivalent expression.


6x−4y

6−4x

6x−4

6x−4x


1. 2x

2. 2(3x−2)

3. 2(3−2x)

4. 2(3x−2y)

Respuesta :

Answer:

6x−4y  ----> 4

6−4x  ------> 3

6x−4  ------> 2

6x−4x------> 1

Step-by-step explanation:

Equivalent expressions are expressions which are equal when simplified to lowest terms. Simplify each expression to lowest terms then match.

6x−4y

6−4x

6x−4

6x−4x  = 2x

1. 2x

2. 2(3x−2)  = 6x -4

3. 2(3−2x)  = 6 - 4x

4. 2(3x−2y) = 6x - 4y

The expressions match the following ways:

6x−4y  ----> 4

6−4x  ------> 3

6x−4  ------> 2

6x−4x------> 1